Focused Renal Sonography Performed and Interpreted by Internal Medicine Residents. (1st November 2013) - Caronia, Jonathan; Panagopoulos, Georgia; Devita, Maria; Tofighi, Babak; Mahdavi, Ramyar; Levin, Benjamin; Carrera, Louis; Mina, Bushra
Abstract : Objectives: Intensivist‐performed focused sonography, including renal sonography, is becoming accepted practice. Whether internal medicine residents can be trained to accurately rule out renal obstruction and identify sonographic findings of chronic kidney disease is unknown. The purpose of this study was to test the ability of residents to evaluate for this specific constellation of findings. Methods: Internal medicine residents were trained in a 5‐hour module on focused renal sonography evaluating renal length, echogenicity, hydronephrosis, and cysts on a convenience sample of medical ward, intermediate care, and medical intensive care unit patients. All patients underwent comprehensive sonography within 24 hours. The primary outcome was represented by the Fleiss κ statistic, which indicated the degree of interobserver agreement between residents and radiologists. Sensitivity, specificity, and positive and negative predictive values were calculated using the comprehensive radiologist‐read examination as the reference. Results: Seventeen internal medicine residents imaged 125 kidneys on 66 patients. The average number of studies performed was 7.3 (SD, 6.6). Residents demonstrated excellent agreement with radiologists for hydronephrosis (κ = 0.73; P < .001; SE, 0.15; sensitivity, 94%; specificity, 93%), moderate agreement for echogenic kidneys (κ = 0.43; P < .001; SE, 0.13; sensitivity, 40%; specificity, 98%), and substantial agreement for renal cysts (κ = 0.61; P < .001; SE, 0.12; sensitivity, 60%; specificity, 96%). Residents showed sensitivity of 100% and specificity of 88% for identification of atrophic kidneys, defined as length less than 8 cm. Conclusions: After a 5‐hour training course, medical residents accurately identified hydronephrosis and key sonographic findings of chronic kidney disease in a cohort of medical patients. Screening for hydronephrosis and renal atrophy can be performed by medical residents after adequate training.